1978
DOI: 10.1002/ijc.2910220214
|View full text |Cite
|
Sign up to set email alerts
|

Some mechanisms involved in cancer cell detachment by necrotic material

Abstract: PROVOQUE PAR DU MATERIEL NBCROTIQUELes facteurs qui influent sur le detachement des cellules jouent probablement un r81e dans la metastatisation et I'envahissement. Des etudes preckdentes, dam lequelles on avait utilise des cylindres preleves sur des tumeurs Walker 256 (W-256) qui se developpent chez les rats, ont montre que les cellules cancereuses viables se detachaient plus facilement si elles Ctaient a proximite de regions nkrotiques o u exposees A un extrait nkcrotique. A I'aide de cultures pures de cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Mitotic inhibitors have been extracted from the necrotic core (see, for example, Levine et ai, 1984), and these prc-sumably diffuse through the spheroid affecting the mjtotic behaviour of some of the cells; however, this mechanism alone cannot be responsible for saturation since it requires that all the cells be inhibited if a continued increase in volume due to cell reproduction is to be prevented; this contradicts experimental observations. During mitosis, the reduced strength in binding between cells may cause individual cells to be shed into the surrounding matrix (Weiss, 1978;Landry et al, 1981) however, the cells that remain will still be reproducing so this mechanism cannot explain growth saturation either. In the models of Greenspan (1972) and subsequent similar studies, the crucial parameter for saturation arises in an expression stating that the contraction rate of the necrotic core is proportional to its volume; it is suggested that this is due to the process of disintegration of necrotic cellular material into simpler permeable compounds with a subsequent loss in volume.…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic inhibitors have been extracted from the necrotic core (see, for example, Levine et ai, 1984), and these prc-sumably diffuse through the spheroid affecting the mjtotic behaviour of some of the cells; however, this mechanism alone cannot be responsible for saturation since it requires that all the cells be inhibited if a continued increase in volume due to cell reproduction is to be prevented; this contradicts experimental observations. During mitosis, the reduced strength in binding between cells may cause individual cells to be shed into the surrounding matrix (Weiss, 1978;Landry et al, 1981) however, the cells that remain will still be reproducing so this mechanism cannot explain growth saturation either. In the models of Greenspan (1972) and subsequent similar studies, the crucial parameter for saturation arises in an expression stating that the contraction rate of the necrotic core is proportional to its volume; it is suggested that this is due to the process of disintegration of necrotic cellular material into simpler permeable compounds with a subsequent loss in volume.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activities of lysosomal enzymes in tumors correlate with tumor malignancy in vivo [8][9][10][11][12] but have often been attributed to the presence of infiltrating host cells or necrotic tumor cells [13,14]. This does not appear to be true for elevated activities of lysosomal proteinases as, in early studies, the highest lysosomal proteinase activities were shown to be associated with the youngest and most rapidly growing tumors [15,16].…”
Section: Lysosomal Cysteine Proteinasesmentioning
confidence: 99%
“…These effects were not due to the chemotactic activities of the extracts, because they were present on both sides of the membrane. Thus, while chemotaxis (necrotaxis; Bessis, 1973) is a factor which could contribute to the accumulation of macrophages around necrotic tissues as observed for example in the W-256 tumour (Weiss, 1978), the enhancement of migration observed by us is due to chemokinesis.…”
Section: Discussionmentioning
confidence: 86%